Correlation between plasma fibrinogen levels and microvascular complications in type 2 diabetes - Hamidullah; Ishtiaq Ahmad; Ashraf; Murad Ali; Manzoor Hussain; Zakirullah (Journal of the Pakistan Medical Association)
Objective: To determine how plasma fibrinogen levels impact the severity of microvascular complications in people with type 2 diabetes while focussing on the molecular mechanisms of fibrinogen’s role in such complications.